Hot surface ionic line emission and cold K-inner shell emission from petawatt-laser-irradiated Cu foil targets - Theobald, W; Akli, K; Clarke, R; Delettrez, J; Freeman, R; Glenzer, S; Green, J; Gregori, G; Heathcote, R; Izumi, N; King, J; Koch, J; et al. (2006)
A hot, 2 to 3 keV electron temperature surface plasma was observed in the interaction of a 0.7 ps petawatt laser beam with solid copper-foil targets at intensities > 1020 W cm2. Copper K-shell spectra were measured in the range of 8 to 9 keV using a single-photon-counting x-ray charged-coupled-device camera. In addition to Kα and KΒ inner-shell lines, the emission contained the Cu Heα and Lyα lines, allowing the temperature to be inferred. These lines have not been observed previously with ultrafast laser pulses. For intensities less than 3× 1018 W cm2, only the Kα and KΒ inner-shell emissions are detected. Measurements of the absolute Kα yield as a function of the laser intensity are in general agreement with a model that includes refluxing and confinement of the suprathermal electrons in the target volume. © 2006 American Institute of Physics.